Critical Low Catastrophe: A Case Report of Treatment-Refractory Hypoglycemia following Overdose of Long-Acting Insulin - Rashi Sandooja; John M. Moorman; Monisha Priyadarshini Kumar; Karla Detoya (Case Reports in Endocrinology)
Overdose of long-acting insulin can cause unpredictable hypoglycemia for prolonged periods of time. The initial treatment of hypoglycemia includes oral carbohydrate intake as able and/or parenteral dextrose infusion. Refractory hypoglycemia following these interventions presents a clinical challenge in the absence of clear guidelines for management. Octreotide has sometimes been used, but its use is generally limited to sulfonylurea overdose. In this case report, we present a case of refractory hypoglycemia following an overdose of 900 units of long-acting insulin glargine that failed to respond to usual modes of therapy mentioned above. Stress-dose corticosteroids were then initiated, followed by subsequent improvement in IV dextrose and glucagon requirements and blood glucose levels. Hence, corticosteroids may serve as an adjunctive therapy in managing hypoglycemia and can be considered earlier in the course of treatment in patients with refractory hypoglycemia to prevent volume overload, especially when large volumes of dextrose infusions are required.